ANALISIS PENGARUH HARGA DAN PROMOSI PENJUALAN TERHADAP EKUITAS MEREK PADA JASA PENERBANGAN GARUDA INDONESIA - Firda Amila; Putut Haribowo; Rusmini Rusmini (Admisi dan Bisnis, 2018)
This study explores the relationship between selected marketing mix elements and the creation of brand equity.  Price affect perceived quality on a brand to be purchased or used.  Effective marketing communication is one of the main tools in establishing brand equity of firms or products.  As we know there are a brand equity, brand equity consist of brand awareness, brand association, perceive quality and brand loyalty.  The main purpose of this final project is to identify the influence of price and sales promotion to brand equity at Garuda Indonesia customer’s on Semarang-Jakarta route.  The data used in this project were the primary data and secondary data.  Data collection techniques used were questionnaries and lieterature.  100 respondents are use sample selected based on purposive sampling.  The analysis techniques used were the validity and reliability, normality test, linearity test, multicolerate test, heterokedatisitas test, multiple result of research analysis, the coefficient of determination, t test and f test.  the result of research, the influence of price is 0,041 with a significance of 0,597 and sales promotion is 0,523 with a significance of 0,000.  Base computation F obtained at 39,791 with a significance of 0,000.  Because the significance value less than 0,05 it means that there is a significant relationship beetwen the variable price and sales promotion to brand equity.  It is concluded that price has a positive impact but insignificant on brand equity.  Sales promotion has a positive and significant on brand equity.  Multiple Regression Analysis 0,439 this means that 43,9% of the variation in brand equity can be explained by the variable of price and sales promotion and the rest (100%-43,9%=56,1%) is explained by other variables.